Photoreactive organic thin films - Sekkat, Zouheir; Knoll, Wolfgang (Academic Press, 2002)
Wolfgang Knoll is a former Directory of Polymer research at the Max Planck Institute. He is extremely well know for his research in this area. Zouheir Sekkat was a Postdoctoral researcher at Max Planck working under Professor Knoll. With Knoll's involvement, we can be confident that the best people in this field will be contributing to the reference.